A study on the impact of saving rate and gross domestic products towards IPO underpricing : evidence in Malaysia - Lim, Kooi Lee (2017)
This study is to determine the level of IPO underpricing and examines the impacts of macroeconomic variables (i,e,. saving rates and GDP) with few control variables towards IPO underpricing on Bursa Malaysia from 2012 to 2016. The result shows that underpricing exists in the first day of trading during the particular period and reported 68.49% of IPOs underpriced. Both linear and OLS regression models are used to distinguish the relationship between various independent variables and dependent variable with control variables. The linear regression show that only GDP affect the IPO underpricing but there is no impact of saving rate towards IPO underpricing. Empirical findings from OLS regression show that both saving rate and GDP with the control variables (i,e,. year of operation or establishment, size of company, underwriter status and issue period) arc significant in influencing the IPO underpricing. In addition, the findings also conclude only GDP is significantly difference on the sub-samples of high and low underpricing.